KOMPOSISI KIMIA DAUN KELAPA SAWIT YANG DIFERMENTASI DENGAN FESES SAPI DAN FESES KERBAU - Dewi Ananda Mucra; Azriani Azriani (State Islamic University of Sultan Syarif Kasim Riau, 2012)
This experiment were conducted to know chemical composition consist of dry matter, ash, crude protein, crude fiber,crude lipid and BETN from palm leaves fermented with buffalo feces dan cattle feces. Inoculants were used cattle feces andbuffalo feces with 5% level from dry matter of palm leaves. Fermentation done for 14 days. Method of experiment wascompletely randomized design with 3 treatments and 3 replications. Result showed that fermentation of palm leaves withcattle feces and buffalo feces were increased crude protein 11.39%-12.49% (P>0,05) and decreased crude fiber 22.71%-19.0% (P>0,05)